Identification and expression levels of pig miRNAs in skeletal muscle - Verardo, L. L.; Nascimento, C. S.; Silva, F. F.; Gasparino, E.; Toriyama, E.; Barbosa, A. R.; Costa, K. A.; Lopes, P. S.; Guimarães, S. E. F.; Périssé, I. V. (Livestock Science, 2013)
MicroRNAs are a class of naturally occurring non-coding RNAs. Typically they are $22 nucleotides long and suppress translation of their targets genes. Several laboratories have attempted to identify miRNAs from pig muscle and the bioinformatics strategies using ESTs have proved to be successful for this aim. In this study we report an in silico identification of ncRNA in pig EST libraries focusing on novel pig miRNAs and further investigated the differential expression of pigs miRNAs (known and novel) by quantitative real-time PCR during preand postnatal stage from Commercial and local breed Piau pigs skeletal muscle tissue. We identified two miRNAs not yet described in pigs: hsa-miR-1207-5p and hsa-miR-665. Besides, we found 288 target genes for hsa-miR-1207-5p and 214 for hsa-miR-665; from them, four are muscle specific genes. Through expression analyses, differences were found between pre- and postnatal stages and genetics groups. The findings of miRNAs and their muscle-specific targets in pigs will be helpful for understanding the function and processing of this RNA class in the future. Besides, the miRNAs differentially expressed between Commercial and Piau breeds suggest that they can be used to uncover phenotypic differences across different genetic groups.
Keywords: EST; Skeletal muscle; miRNA; Targets; Expression